IgA Nephropathy with Thrombotic microangiopathy: Is this secondary thrombotic microangiopathy or IgA nephropathy-triggered atypical Hemolytic Uremic Syndrome? - Diniz,Hugo (2019)
IgA Nephropathy (IgAN) is the most prevalent biopsy-proven primary glomerular disease worldwide. Historically, thrombotic microangiopathy (TMA) was associated with IgAN in cases of severe hypertension or advanced chronic kidney disease, but recent data suggest that complement activation plays a crucial role in the development of TMA in IgAN. We report a case of Crescentic IgAN with complement-mediated TMA (C-TMA) in a 27-year old male patient with a pathological missense mutation in heterozygosity in the CFH gene and a rare variant in the C3 gene, treated with steroids, cyclophosphamide and plasmapheresis without recovery of kidney function. We also discuss other treatment possibilities and kidney transplant options. Additionally, we will review the latest advances that are enhancing our understanding of the association between IgAN and TMA